TI_GERICHTE 52.2011.328 vom 5. Januar 2012 , Prescrizioni locali concernenti il traffico. Divieto generale di circolazione - TI Tribunale d'appello (2012)
Prescrizioni locali concernenti il traffico. Divieto generale di circolazione